Pertanian Tradisional Sebagai Upaya Ketahanan Pangan di Pulau Seram, Provinsi Maluku - Ansiska, Paisal; Sari, Indriati Meilina (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
Traditional agriculture is crucial in food security in remote areas such as Seram Island, Maluku Province, by providing primary food sources and preserving biodiversity and local wisdom. However, modernization and climate change threaten the sustainability of this system. This study explores traditional farming methods on Seram Island that can be integrated with modern technology to enhance food security. The findings indicate that local communities use mixed farming methods and organic fertilizers, which increase soil fertility productivity and reduce the risk of crop failure. These results align with studies highlighting the advantages of mixed farming systems and the effectiveness of organic fertilizers. Adapting modern technology, such as drought-resistant rice varieties and applying organic fertilizers on cassava and sweet potatoes, also proved to increase crop yields and productivity, supporting the literature on the benefits of climate-resistant crop varieties and organic fertilizers. This research contributes to the literature on the role of traditional agriculture in food security. It demonstrates that integrating modern technology with traditional practices can create a more productive and sustainable agricultural system. An approach that preserves local wisdom while adopting technological innovations could be an effective model for improving food security and farmer welfare in other regions facing similar challenges.